A conserved odorant receptor identified from antennal transcriptome of Megoura crassicauda that specifically responds to cis-jasmone - Bo WANG; Tian-yu HUANG; Yuan YAO; Frederic FRANCIS; Chun-cai YAN; Gui-rong WANG; Bing WANG (Journal of Integrative Agriculture, 2022)
Herbivore-induced plant volatiles (HIPVs) play a key role in the interactions between plants and herbivorous insects, as HIPVs can promote or deter herbivorous insects’ behavior. While aphids are common and serious phloem-feeding pests in farmland ecosystems, little is known about how aphids use their sensitive olfactory system to detect HIPVs. In this study, the antennal transcriptomes of the aphid species Megoura crassicauda were sequenced, and expression level analyses of M. crassicauda odorant receptors (ORs) were carried out. To investigate the chemoreception mechanisms that M. crassicauda uses to detect HIPVs, we performed in vitro functional studies of the ORs using 11 HIPVs reported to be released by aphid-infested plants. In total, 54 candidate chemosensory genes were identified, among which 20 genes were ORs. McraOR20 and McraOR43 were selected for further functional characterization because their homologs in aphids were quite conserved and their expression levels in antennae of M. crassicauda were relatively high. The results showed that McraOR20 specifically detected cis-jasmone, as did its ortholog ApisOR20 from the pea aphid Acyrthosiphon pisum, while McraOR43 did not respond to any of the HIPV chemicals that were tested. This study characterized the ability of the homologous OR20 receptors in the two aphid species to detect HIPV cis-jasmone, and provides a candidate olfactory target for mediating aphid behaviors.